A COMPARATIVE ANALYSIS OF TENSE-ASPECT SYSTEMS IN ENGLISH AND UZBEK LANGUAGES - Sh. Mardonov; Z.Omonova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The article compares how tense and aspect work in English and Uzbek. The main aim is to explain similarities and differences in a clear and simple way. A contrastive and descriptive method is used. English forms are examined through auxiliary verbs and fixed patterns. Uzbek forms are examined through suffixes, short auxiliary elements, and context. The analysis focuses on simple, progressive, perfect, and earlier- past meanings. Short literary extracts are also used, because real texts show grammar more clearly than isolated examples. The review section includes both basic grammar studies and recent research. The discussion of extracts from O. Henry, Abdulla Qodiriy, and Xoliyor Safarov shows that English usually builds tense-aspect meaning through separate words such as be and have, while Uzbek often places several meanings inside one verb form through suffixes. The study shows that both languages express completion, duration, and sequence, but the grammatical path is different. English is more segmented. Uzbek is more compact. The article can be useful for students, teachers, and translators.